2005
DOI: 10.1108/02634500510630186
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of consumer trust: likelihood to pay online

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 20 publications
2
13
0
2
Order By: Relevance
“…Further, it is evident that there is a positive relationship between trust and consumers' perception of E-Payment Systems. These findings are consistent with prior research done by Abrazhevich, (2001), Kurnia and Benjamin, (2007), Black (2005); Abrazhevich (2004); Özkan et al, (2010) and Zhou (2011).…”
Section: B Effect Of Trust On Consumers' Perception Epssupporting
confidence: 93%
“…Further, it is evident that there is a positive relationship between trust and consumers' perception of E-Payment Systems. These findings are consistent with prior research done by Abrazhevich, (2001), Kurnia and Benjamin, (2007), Black (2005); Abrazhevich (2004); Özkan et al, (2010) and Zhou (2011).…”
Section: B Effect Of Trust On Consumers' Perception Epssupporting
confidence: 93%
“…Dholakia and Chiung (2003) investigated the role of gender in the differences in attitude towards online shopping. Black (2005) identified how age, income, gender, education, cost of living, crime index affect purchase intention. V enkatesh and Agarwal (2006) in their seminal work identified how age and gender affect website usability.…”
Section: The Moderating Effect Of Customer Demographics and Psychogramentioning
confidence: 99%
“…The importance of trust has been highlighted by past research (Black, 2005;Fleischmann and Ivens, 2019;Ofori et al, 2017;Sas and Khairuddin, 2015;Kumar et al, 2020), suggesting that it is fundamental and constitutes a key driver of consumer adoption of the technology. A notable exception is the study of trust by Marella et al (2020), who analysed online discussions of Bitcoin and identified functionality, reliability and helpfulness as key constructs.…”
Section: Introductionmentioning
confidence: 99%